The new Italian code of medical ethics. - Fineschi, V (1997)
In June 1995, the Italian code of medical ethics was revised in order that its principles should reflect the ever-changing relationship between the medical profession and society and between physicians and patients. The updated code is also a response to new ethical problems created by scientific progress; the discussion of such problems often shows up a need for better understanding on the part of the medical profession itself. Medical deontology is defined as the discipline for the study of norms of conduct for the health care professions, including moral and legal norms as well as those pertaining more strictly to professional performance. The aim of deontology is therefore, the in-depth investigation and revision of the code of medical ethics. It is in the light of this conceptual definition that one should interpret a review of the different codes which have attempted, throughout the various periods of Italy's recent history, to adapt ethical norms to particular social and health care climates.